Cloud-based technologies for postgraduate teacher education - S. V. Kaplun (Academy of Cognitive and Natural Sciences, 2013)
Today, reports about the use of the Internet in the educational process is almost no surprise, because it seems that everyone has long agreed on the need for information and communication support training in general education and higher education. However, the actual practice of using these opportunities in many Ukrainian schools, in our opinion, is very far from what is necessary. Often a teacher's work on the Internet is limited to searching and downloading "methodological developments", as well as communication in social networks. Therefore, the urgent task of the system of training and professional development of teachers is to form the necessary ideas about the methodology and didactic capabilities of the global network and, in particular, cloud technologies.